Treating Rare Diseases in Africa: The Drugs Exist but the Need Is Unmet - Lucio Luzzatto; Lucio Luzzatto; Julie Makani (Frontiers Media S.A., 2022)
Rare diseases (RD) pose serious challenges in terms of both diagnosis and treatment. Legislation was passed in the US (1983) and in EU (2000) aimed to reverse the previous neglect of RD, by providing incentives for development of "orphan drugs" (OD) for their management. Here we analyse the current situation in Africa with respect to (1) sickle cell disease (SCD), that qualifies as rare in the US and in EU, but is not at all rare in African countries (frequencies up to 1-2%); (2) paroxysmal nocturnal haemoglobinuria (PNH), that is ultra-rare in Africa as everywhere else (estimated <10 per million). SCD can be cured by bone marrow transplantation and recently by gene therapy, but very few African patients have access to these expensive procedures; on the other hand, the disease-ameliorating agent hydroxyurea is not expensive, but still the majority of patients in Africa are not receiving it. For PNH, currently most patients In high income countries are treated with a highly effective OD that costs about $400,000 per year per patient: this is not available in Africa. Thus, the impact of OD legislation has been practically nil in this continent. As members of the medical profession and of the human family, we must aim to remove barriers that are essentially financial: especially since countries with rich economies share a history of having exploited African countries. We call on the Global Fund to supply hydroxyurea for all SCD patients; and we call on companies who produce ODs to donate, for every patient who receives an expensive OD in a high income country, enough of the same drug, at a symbolic price, to treat one patient in Africa.